Simplify to obtain a sum of products: (A+B)(C+B)(D?+B)(ACD?+E)
1 answer:
Answer:
(ACD'+BE)
Explanation:
(A+B)(C+B)(D'+B)(ACD'+E)
Product of (A+B)(C+B)
(A+B)(C+B)=AC+AB+BC+B^2 = AC+B(A+C+B)=AC+B
Product of (D'+B)(ACD'+E) with AC+B
(AC+B)(D'+B)(ACD'+E)
(AC+B)(D'+B)=ACD' + ACB +BD +B = ACD'+B(AC+D+1)=ACD'+B
Then we get:
(ACD'+B)(ACD'+E) = ACD'+ACD'E+ACD'B+BE
ACD'(1+E+B)+BE =ACD'+BE
You might be interested in
User’s browser renders HTML code from destination server into web page
Answer:
B
Explanation:
This problem statement does not clearly define the issues.
Answer:
In the SOA tab of the zone's Properties dialog box, increase the refresh interval.
Explanation:
Can you be more specific?